Implementasi Akad Ijarah Dalam Meningkatkan Pendapatan Mitra Ojek Online Abang Kurir Bangkalan - Argarini, Galuh Mustika; Nisa', Khoirun (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This research is included in qualitative research using field research methods. The subjects of the study are the owners, employees/drivers, and consumers/business partners of Abang Courier Bangkalan (ABANK). Sampling uses the Snow Ball Sampling technique because it can expand the research subject. The purpose of this study is first, to find out how the implementation of the ijarah contract in online motorcycle taxis Abang Courier Bangkalan (ABANK). While the disadvantages are not including a list of fares on ABANK Passenger services, not including a list of shipping costs on social media when ads are published, it become an anomaly in society about how much food is sold. In this case, there is potential harm to consumers in terms of comfort and satisfaction, but there is no material loss. Because no party is harmed, and both parties are willing and ridho, then the ijarah contract that is carried out is legally valid. Apart from that, some of these shortcomings do not affect sales results, this is proven by the increasing number of partners joining the Abang Courier Bangkalan (ABANK) online motorcycle taxi and the increase in profits from these partners, so that partners are increasingly active in increasing the types of goods sold.